Pollen calendar of the city of Salamanca (Spain). Aeropalynological analysis for 1981-1982 and 1991-1992. - Hernández Prieto, M; Lorente Toledano, F; Romo Cortina, A; Dávila González, I; Laffond Yges, E; Calvo Bullón, A (Allergol Immunopathol (Madr), 1998)
We report a study on the contents of airborne pollen in the city of Salamanca (Spain) aimed at establishing a pollen calendar for the city for the yearly periods of maximum concentrations, relating these with quantifiable atmospheric variables over two two-year periods with an interval of 10 years between them: 1981-82 and 1991-92. The pollen was captured with Burkard spore-traps, based on Hirst's volumetric method. Determinations were made daily and were used to make preparations, previously stained with basic fuscin, for study under light microscopy at x 1,000 magnification. 946 preparations were analyzed, corresponding to the same number of days distributed over 150 weeks of the periods studied. The results afforded the identification of 48 different types of pollen grain: Grasses (Poaceae), Olea europea (olive), Quercus rotundifolia (Holm-oak), other Quercus spp. (Q. pyrenaica, Q. suber, Q. faginea, etc.), Cupressaceae (Cupressus sempervivens, C. arizonica, Juniperus communis etc.), Plantago (Plantago lanceolata, Plantago media, etc.), Pinaceae (Pinus communis, Abies alba, etc.), Rumex sp. (osier), Urtica dioica (nettle), Parietaria (Parietaria officinalis, P. judaica), Chenopodio-Amaranthaceae (Chenopodium sp., Amaranthus sp., Salsola kali, etc.), Artemisia vulgaris (Artemisia), other Compositae (Taraxacum officinalis, Hellianthus sp. etc.), Castanea sativa (Chestnut), Ligustrum sp. (privet), Betula sp. (birch), Alnus sp. (common alder), Fraxinus sp (ash), Populus sp. (poplar), Salix sp. (willow), Ulmus sp. (elm), Platanus sp. (plantain, plane), Carex sp. (sweet flag), Erica sp. (common heather), Leguminosae or Fabaceae:--Papillionaceae (Medicago sp.; Cercis sp., Robina sp.)--Cesalpinoideae Acacia sp. (Acacia),--Mimosoideae: Sophora japonica, Umbelliferae (Foeniculum sp., Cirsium sp., etc.), Centaurea sp., Cistus sp. (rock rose), Typha sp (bulrush), Mirtaceae (Myrtus communis), Juglans regia (Walnut), Galium verum, Filipendula sp. (spirea/drop wort), Rosaceae (Pyrus sp., Prunus sp., etc.), Tilia sp. (Linden), Morus sp. (mulberry), Taxus baccata (yew), Papaveraceae (Papaver rhoeas etc.), Labiata (Lavandula sp.), Cannabaceae (Humulus sp. etc.), Liliaceae (Lilium sp.), Echium sp. (viper's bugloss). The most abundant taxa, detected in the highest quantities (grains/m3 air), by order of counting were as follows: holm-oak, olive, grasses, Plantago and Parietaria. With the data obtained we have established a pollen calendar for Salamanca and report the period in which each type of pollen is found along the years and the periods with the highest airborne concentrations of such pollens. The diversity and the spectrum of the pollen in the city of Salamanca correspond to the typical plant communities found on the dehesas (large ranges of grasslands) of Castile, where Salamanca is located, although the wind directions and the peculiar climatic characteristics of the area govern the peaks of maximum presence of the different taxa. As examples, in the case of olive, which is cultivated at some distance from the city, its maximum presence coincides with south-westerly winds; in the case of grasses, the peaks of maximum counts coincide with a sharp rise in mean temperature, close to or higher than 20 degrees C and between five and six weeks after rainfall equal to or greater than 5 L/m2.
APS
Keywords: pollen concentrations; Spain